Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--20972
|View full text |Cite
|
Sign up to set email alerts
|

Assessing an Adaptive Expertise Instrument in Computer-aided Design (CAD) Courses at Two Campuses

Abstract: In today's highly competitive market, CAD tools are widely used and thought to reduce time to market and increase engineering productivity. However, to take advantage of these putative benefits requires proper use of CAD tools. Merely teaching declarative knowledge (particular keystrokes and button picks) in CAD is not sufficient; students should acquire deeper procedural knowledge (design strategy) in CAD. This will allow them to gain a level of expertise that is adaptive in nature. Recent research in enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Learning CAD requires cognitive understandings. The importance of this cognitive aspect is corroborated by Johnson, Ozturk and Yalvac et al (2012) that "cognitive skills are critical for effective use of modern CAD programs". This implies that in CAD learning, there is not one standard and rigid way to solve a technical problem.…”
Section: Results and Discussion Of Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Learning CAD requires cognitive understandings. The importance of this cognitive aspect is corroborated by Johnson, Ozturk and Yalvac et al (2012) that "cognitive skills are critical for effective use of modern CAD programs". This implies that in CAD learning, there is not one standard and rigid way to solve a technical problem.…”
Section: Results and Discussion Of Researchmentioning
confidence: 96%
“…Flavell argues that metacognitive is the internal processing that makes use of cognitive strategies to monitor and control other learning and memory processes ". In addition, Johnson, Ozturk and Yalvac et al (2012) argue on the importance of developing CAD learning by focusing on the metacognitive aspect (Gagne, Briggs and Wager, 1992: 71).…”
Section: Results and Discussion Of Researchmentioning
confidence: 99%
“…Computer‐aided design (CAD) tools have gained great relevance in reinforcing students' education in engineering studies, as it allows them to implement and check technical drawings in a fast and efficient way [18, 21, 34]. However, most CAD teaching techniques comprise the presentation of the main programme commands, and the implementation of specific tutorials [38, 48], which are not enough to evaluate a student's ability to manage CAD programmes. Engineering students could use CAD tools to solve almost any engineering problem [37].…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al [14] confirmed the reliability of the survey tool developed by Fisher and Peterson in a 2012 study, although low participation rates of various sub-populations reduces the ability to make comparisons. Pierrakos et al [15] also performed a study examining the reliability of the survey tool and again, found it to be a reliable instrument, in addition to showing differences in AE levels displayed by senior students in two design programs, one of which was designed to teach adaptive expertise and included mastery-based learning as well as "Explicit Values of the Course being grit, metacognition, innovation, collaboration, and quality".…”
Section: Introductionmentioning
confidence: 91%